A, Perancangan Media Pembelajaran Berbasis Multimedia Genially: Jurnal - Rindawati; Hera Heru Sri Suryanti; Daryono Daryono (UNIVERSITAS SLAMET RIYADI, 2024)
This study aimed to determine the feasibility of designing multimedia-based learning media genially on Jaringan computer dan Internet material in class 7A SMPN 18 in 2023, and to determine the effectiveness of designing multimedia-based learning media genially to attract students' interest in learning Informatics. The research method used was R&D with the research procedure using the ADD model from Dick and Carey. The ADD procedure consisted of Analysis, Design, and Development. Data collection techniques were obtained through interviews, questionnaires and documentation, as well as Blackbox Testing. Product feasibility Validation was carried out by Expert Judgement which was analyzed using a Likert Scale. This results of this study ware the eligibility validation of the informatics teacher stating that the Adventure Missions game had a feasibility level 96% with verydecent criteria. In addition, this study received positive responses from students in class 7A at SMP Negeri 18 Surakarta, where the result was 95,1% with feasible criteria. Therefore, this Adventure Missions game could be said to be effective in attracting students' interest in learning Informatics.